Association between SMAD4 Mutations and GATA6 Expression in Paired Pancreatic Ductal Adenocarcinoma Tumor Specimens: Data from Two Independent Molecularly-Characterized Cohorts - Joshua D. Greendyk; William E. Allen; H. Richard Alexander; Toni Beninato; Mariam F. Eskander; Miral S. Grandhi; Timothy J. Kennedy; Russell C. Langan; Jason C. Maggi; Subhajyoti De; Colin M. Court; Brett L. Ecker (Biomedicines, 2023)
Several molecular biomarkers have been identified to guide induction treatment selection for localized pancreatic ductal adenocarcinoma (PDAC). SMAD4 alterations and low GATA6 expression/modified “Moffitt” basal-like phenotype have each been associated with inferior survival uniquely for patients receiving 5-FU-based therapies. SMAD4 may directly regulate the expression of GATA6 in PDAC, pointing to a common predictive biomarker. To evaluate the relationship between SMAD4 mutations and GATA6 expression in human PDAC tumors, patients with paired SMAD4 mutation and GATA6 mRNA expression data in the TCGA and CPTAC were identified. In 321 patients (TCGA: n = 180; CPTAC: n = 141), the rate of SMAD4 alterations was 26.8%. The rate of SMAD4 alteration did not vary per tertile of normalized GATA6 expression (TCGA: p = 0.928; CPTAC: p = 0.828). In the TCGA, SMAD4 alterations and the basal-like phenotype were each associated with worse survival (log rank p = 0.077 and p = 0.080, respectively), but their combined presence did not identify a subset with uniquely inferior survival (p = 0.943). In the CPTAC, the basal-like phenotype was associated with significantly worse survival (p < 0.001), but the prognostic value was not influenced by the combined presence of SMAD4 alterations (p = 0.960). SMAD4 alterations were not associated with poor clinico-pathological features such as poor tumor grade, advanced tumor stage, positive lymphovascular invasion (LVI), or positive perineural invasion (PNI), compared with SMAD4-wildtype. Given that SMAD4 mutations were not associated with GATA6 expression or Moffitt subtype in two independent molecularly characterized PDAC cohorts, distinct biomarker-defined clinical trials are necessary.